2005
DOI: 10.1523/jneurosci.2466-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nerve Injury-Induced Neuropathic Pain in Kinin B1Receptor Knock-Out Mice

Abstract: Injury to peripheral nerves often results in a persistent neuropathic pain condition that is characterized by spontaneous pain, allodynia, and hyperalgesia. Nerve injury is accompanied by a local inflammatory reaction in which nerve-associated and immune cells release several pronociceptive mediators. Kinin B 1 receptors are rarely expressed in nontraumatized tissues, but they can be expressed after tissue injury. Because B 1 receptors mediate chronic inflammatory painful processes, we studied their participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 50 publications
5
49
3
Order By: Relevance
“…Recent findings suggest the requirement for the B 1 receptor in neuropathic pain resulting from injuries to peripheral nerves (Ferreira et al, 2005). The data with LF22-0542 support a significant role of the B 1 receptor in mediating nerve injury-induced thermal hypersensitivity but not tactile hypersensitivity.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recent findings suggest the requirement for the B 1 receptor in neuropathic pain resulting from injuries to peripheral nerves (Ferreira et al, 2005). The data with LF22-0542 support a significant role of the B 1 receptor in mediating nerve injury-induced thermal hypersensitivity but not tactile hypersensitivity.…”
Section: Discussionmentioning
confidence: 78%
“…However, B 1 KO animals did not develop thermal hypersensitivity but nevertheless showed SNL-induced tactile hypersensitivity that did not differ from the WT animals. Pesquero and colleagues have reported that B 1 KO mice did not develop either tactile or thermal hypersensitivity after nerve injury (Ferreira et al, 2005). In those studies the authors used mice from the same source as in the present studies but used a different model nerve injury (i.e., partial ligation of the sciatic nerve).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the systemic administration of B 1 R antagonist des-Arg 9 -Leu 8 -BK was able to reduce thermal and mechanical hypernociception induced by sciatic nerve constriction in rats (Levy and Zochodne, 2000;Yamaguchi-Sase et al, 2003). Interestingly, the gene deletion of B 1 R practically abolished the hypernociception produced by sciatic nerve injury in mice (Ferreira et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Experimental intraplantar injections of B1 or B2 receptor agonists increase response to pain 12 , while antagonists injection inhibits hyperalgesia in NP models 13 . Decreased hyperalgesia secondary to nervous injury obtained by deleting the gene responsible for B1 receptors in mice confirms the important role of bradykinin as central inflammatory mediator in NP 14,15 .…”
Section: Bradykininsmentioning
confidence: 60%